Pengaruh Akreditasi Rumah Sakit Bagi Perlindungan Hukum Pasien dalam Sengketa Medis (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Hospitals, as healthcare institutions, bear the responsibility of delivering safe, high-quality, and patient-centered services. Hospital accreditation serves as a crucial mechanism to ensure service quality and legal protection for patients, particularly in medical dispute cases. This study aims to analyze the impact of accreditation on patient legal protection, both preventively and repressively. The research employs a normative legal method with statutory and conceptual approaches, utilizing primary, secondary, and tertiary legal materials. Data were analyzed through document studies covering Law Number 17 of 2023 on Health, government regulations, presidential regulations, and technical regulations from the Ministry of Health regarding accreditation standards and procedures. The findings indicate that accreditation functions as a continuous evaluation mechanism to ensure medical services comply with safety standards and clinical governance, strengthens patients’ rights to information, informed consent, and quality care, and reduces the risk of medical disputes. However, implementation challenges exist, including limited resources, compliance performed as formalities, and inconsistent supervision. Therefore, accreditation is not merely an administrative symbol but a strategic legal instrument that enhances patient safety culture and hospital accountability, ensuring that healthcare delivery meets professional, ethical, and legal standards.